The big win : learning from the legends to become a more successful investor - Weiss, Stephen L., 1955- (John Wiley & Sons, Inc., 2012)
A rousing and practical look at the extremely successful investments of top investors In his first book, The Billion Dollar Mistake, author Stephen L. Weiss showcased the biggest blunders of some of the world's legendary investors-which lost them billions of dollars on a single investment. Incredibly, the mistakes they made were the same mistakes made by everyday investors but for the magnitude of the loss. Weiss's second book, The Big Win: Learning from the Legends to Become a More Successful Investor, highlights financial successes, explaining how the world's most successful investors make a.